Direct Asymmetric α‐Selective Mannich Reaction of β, γ‐Unsaturated Ketones with Cyclic α‐Imino Ester: Divergent Synthesis of Cyclocanaline and Tetrahydro Pyridazinone Derivatives. Issue 16 (18th February 2021) - Geng, Yu‐Huan; Hua, Yuan‐Zhao; Jia, Shi‐Kun; Wang, Min‐Can
Abstract: The first regio‐, diastereo‐, and enantioselective direct Mannich reaction of β, γ, ‐unsaturated ketones with benzoxazinone cyclic imines was enabled by Lewis acid/Brønsted base cooperative catalysis. The dinuclear zinc complex catalyzed the reaction of a broad range of β, γ‐unsaturated ketones to proceed at the α‐site exclusively, leading to corresponding adducts with two consecutive tertiary carbon stereocenters in diastereomeric ratios of up to >20:1 and enantioselectivities generally in the 90–99 % ee range. These products were used as general intermediates in the synthesis of multisubstituted cyclocanalines, tetrahydro pyridazinones, and 4 H ‐furo[2, 3‐ b ][1, 4]benzoxazine derivatives. Abstract : Two roads diverged : Direct asymmetric α‐selective Mannich reaction of β, γ‐unsaturated ketones with cyclic α‐imino ester is realized by a dinuclear zinc catalyst giving Mannich adducts with high enantioselectivity. These products could be used as common intermediates in the synthesis of multisubstituted cyclocanalines, tetrahydro pyridazinones, and 4 H ‐furo[2, 3‐ b ][1, 4]benzoxazine derivatives.